Assessment of energetic requirements of reared molluscs and of their main competitors - Deslous-paoli, Jean-marc (In : Aquacutlture : shellfish culture development & Management. Ed. Ifremer. La Rochelle, 4-9 mars 1985, pp 331-346, 1985)
In the context of aquaculture in open sea• the amount: and qua11ty of food is variable according to the season and the physical flux in the ecosystem (carrying capacity ecosystems ). Thus to predict the potential al production of a cultivated ecosystem, it is mandatory 'co know ~he seasona1 changes in organisms energy balance of cultivated organisms. These changes result from the environmental variability either in the temperature or more significantly in the nutrients supply (Bayne and Newell, 1983). The techniques of physiological energetics allow to understand the adaptations of the energy balance in bivalve molluscs and to calculate the complete energy budget all over the seasonal variations of the field. Such studies are few, they include research on individual organisms or on an whole population. These researchs have been done on Scrobicularia plana (Hugues, 1970), Crassostrea gigas (Bernard, 1974, Kim, 1980, Héral & al., 1983, Deslous-Paoli & Héral 1984), Mercenari mercenaria (Hibbert, 1977), Mytilus edulis (Bayne & Widdows, 1978, Widdows, 1978, Rosenberg & loo, 1983, Thompson, 1984a, Hawkins & al. 1985), Mytilus chilsenis (Navarro & Winter, 1982), Perna perna (Berry & Schleyer, 1983) and a gastropod competitor Crepidula fornicate (Deslous-Paoli & al. 1985)